2017
DOI: 10.1038/s41598-017-09428-2
|View full text |Cite
|
Sign up to set email alerts
|

GABA accretion reduces Lsi-1 and Lsi-2 gene expressions and modulates physiological responses in Oryza sativa to provide tolerance towards arsenic

Abstract: GABA counteracts wide range of stresses through regulation of GABA shunt pathway in plants. Although, GABA assisted tolerance against As toxicity in plants is still unexplored. We have examined GABA induced tolerance in rice seedlings with two exposure periods of GABA i.e., short term and long term. Results showed that accumulation of GABA reduced the expressions of Lsi-1 and Lsi-2 transporter genes, which ultimately decreased the accumulation of As in rice seedlings. The accumulation of GABA also modulated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…129 When rice seedlings grew under arsenic (As (III)) stress, GABA application induced GABA-shunt-related gene expression, activated the antioxidant enzyme system, and strongly inhibited As accumulation, thus conferring a tolerance to As (III) in the seedlings. 130 Interestingly, long-term accumulation of GABA is more highly efficient in inducing As (III) tolerance than higher GABA levels in the short term, which actually causes toxicity. 130 On the other hand, Cd stress seemingly reduces endogenous GABA content in duckweed, and under Cd stress, exogenous GABA enhanced rhizoid abscission, whereas Glu addition promotes rhizoid abscission.131 GAD genes are uniformly up-regulated in maize and rice roots by Cd stress, and the overexpression of ZmGAD1 and ZmGAD2 in Cd-sensitive yeast and tobacco leaves enhances Cd tolerance in the host cells.132 All of the aforementioned studies indicate that GABA content does not always increase in response to different metal stresses and may be more related to metal concentrations.…”
Section: Heavy Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…129 When rice seedlings grew under arsenic (As (III)) stress, GABA application induced GABA-shunt-related gene expression, activated the antioxidant enzyme system, and strongly inhibited As accumulation, thus conferring a tolerance to As (III) in the seedlings. 130 Interestingly, long-term accumulation of GABA is more highly efficient in inducing As (III) tolerance than higher GABA levels in the short term, which actually causes toxicity. 130 On the other hand, Cd stress seemingly reduces endogenous GABA content in duckweed, and under Cd stress, exogenous GABA enhanced rhizoid abscission, whereas Glu addition promotes rhizoid abscission.131 GAD genes are uniformly up-regulated in maize and rice roots by Cd stress, and the overexpression of ZmGAD1 and ZmGAD2 in Cd-sensitive yeast and tobacco leaves enhances Cd tolerance in the host cells.132 All of the aforementioned studies indicate that GABA content does not always increase in response to different metal stresses and may be more related to metal concentrations.…”
Section: Heavy Metalmentioning
confidence: 99%
“… 130 Interestingly, long-term accumulation of GABA is more highly efficient in inducing As (III) tolerance than higher GABA levels in the short term, which actually causes toxicity. 130 On the other hand, Cd stress seemingly reduces endogenous GABA content in duckweed, and under Cd stress, exogenous GABA enhanced rhizoid abscission, whereas Glu addition promotes rhizoid abscission. 131 GAD genes are uniformly up-regulated in maize and rice roots by Cd stress, and the overexpression of ZmGAD1 and ZmGAD2 in Cd-sensitive yeast and tobacco leaves enhances Cd tolerance in the host cells.…”
Section: Abiotic and Biotic Stressmentioning
confidence: 99%
“…Expression of the Lsi1 gene in rice is downregulated by Si supply, dehydration stress and abscisic acid (more strongly in Si-depleted plants), suggesting regulation of active Si uptake in response to changes in the transpiration stream and plant internal water balance [ 123 ]. Further studies have demonstrated how the expression of Lsi1 , Lsi2 and Lsi6 genes is regulated by plant hormones [ 124 ] and internal Si and metal concentrations [ 125 , 126 ].…”
Section: Silicon Uptake By Plantsmentioning
confidence: 99%
“…GABA is a four-carbon non-protein amino acid that increases in plant tissues under stress [29]. The GABA shunt has a functional role in biotic and abiotic stress in plants through the improvement in the antioxidant activity to restrict ROS species production, plant cell signaling, and metabolism under stress [29,30]. The GABA shunt pathway is composed of three enzymatic reactions.…”
Section: Introductionmentioning
confidence: 99%